2020
DOI: 10.1158/1541-7786.mcr-19-1245
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RET Kinase in Neuroendocrine Prostate Cancer

Abstract: The increased treatment of metastatic castration-resistant prostate cancer (mCRPC) with second-generation antiandrogen therapies (ADT) has coincided with a greater incidence of lethal, aggressive variant prostate cancer (AVPC) tumors that have lost dependence on androgen receptor (AR) signaling. These ARindependent tumors may also transdifferentiate to express neuroendocrine lineage markers and are termed neuroendocrine prostate cancer (NEPC). Recent evidence suggests kinase signaling may be an important drive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…(1) the high frequency of AR aberrations were often identified in ADT-resistance PC patients suggesting that AR-mutation is one of the main drivers of progression and the poor prognosis of PC patients ( 40); (2) some poorly differentiated or highly aggressive PC cells or specimens show low levels of AR or PSA (41); (3) some ARindependent pathways function as an alternative mechanism contributing to PC and sustain the proliferation or invasion in a completely hormone-independent manner (42); and (4) some factors or pathways mediating the stemness signatures or selfrenewal often participate in the recurrence or ADT-resistance of PC (43). Therefore, it is valuable to explore these detailed mechanisms and the therapeutic strategies of endocrineindependent (androgen receptor [AR]-independent) PC in order to improve the survival rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…(1) the high frequency of AR aberrations were often identified in ADT-resistance PC patients suggesting that AR-mutation is one of the main drivers of progression and the poor prognosis of PC patients ( 40); (2) some poorly differentiated or highly aggressive PC cells or specimens show low levels of AR or PSA (41); (3) some ARindependent pathways function as an alternative mechanism contributing to PC and sustain the proliferation or invasion in a completely hormone-independent manner (42); and (4) some factors or pathways mediating the stemness signatures or selfrenewal often participate in the recurrence or ADT-resistance of PC (43). Therefore, it is valuable to explore these detailed mechanisms and the therapeutic strategies of endocrineindependent (androgen receptor [AR]-independent) PC in order to improve the survival rate of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent NCI workshop on Lineage Plasticity in AR-independent prostate cancer highlighted an urgent need to identify novel therapeutic targets to treat CRPC that bypasses AR-directed therapies [35]. Both MET and RET have been proposed as targets for treatment in patients with CRPC that display a decrease in AR expression or have converted to a SCNPC phenotype respectively [4][5][6]. In this report, we confirmed that elevated levels of MET and RET transcripts were associated with the SCNPC phenotype in patient metastases from our rapid autopsy program [2] and in the SU2C/PCF cohort [16], and similar characteristics were observed in LuCaP SCNPC PDX models.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AR-loss or attenuated AR signaling is associated with increased expression of the MET oncogene in CRPC, and MET has been suggested as a therapeutic target in AR therapy-resistant and AR-null CRPC [ 4 ]. Moreover, the RET proto-oncogene is also expressed in CRPC and preclinical studies targeting RET kinase activity in SCNPC have demonstrated reduced tumor growth [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically distinct therapeutic strategies are considered against NEPC compared to the AR-driven adenocarcinomas. The studies from Beltran and Drake laboratories established that targeting Aurora A [ 426 ] and Ret [ 427 ] kinases could bring benefit to NEPC patients. Specifically, a phase II clinical trial of the Aurora kinase A inhibitor alisertib for CRPC and NEPC patients established that in a subset of patients with molecular features supporting Aurora A and N-myc activation significant clinical benefit from single agent alisertib could be achieved [ 426 ].…”
Section: Therapeutic Potential Of Post-translational Modificationsmentioning
confidence: 99%